The Development of Islamic Religion Education Curriculum at University Seen From the Perspective of Maqashid - Arifi, Ahmad; ., . (International Journal of Engineering and Technology, 2018)
In this present globalization era, many fields of changes occur, especially in education field which runs rapidly and dynamically. An individualâ€™s science, technology, and competence will quickly obsolete it they are not upgraded. Thus, it is required education curriculum development, especially Islamic Religion Education so that they are able to answer era challenge. This study is aimed to explain the development of Islamic Religion Education (IRE) curriculum development at universities seen from the perspective of Maqashid. In this context, curriculum development which is based on maqashid is a curriculum development based on maqashid is a curriculum development which is based on contextual objective which adapt dynamic era development that is a curriculum which is able to cover various recent developments and objective which direct learners to the natural benefit (rahmatan lil alamin). Research method which is utilized is natural qualitative. This research has been successful to collaborate philosophical base of curriculum development of Islamic Religion Education Study Program seen from maqashid perspective. This research concludes that the development of curriculum of Islamic Religion Education at Tarbiyah and Teachers Training Science Faculty, UIN Sunan Kalijaga orients on values of rahmatan lil â€˜alamin manifested in three things: First, the study program vision has possessed value philosophy which supports the achieved civil society through interconnection integration of science in the context of developing world peace and civilization. Second, preparing learners to be able to fulfill national qualification standard by developing curriculum which refer on Indonesian Qualification Framework (IQF) and High Education National Standard (SNPT) and fulfill University International Qualification, which is ASEAN University Network-Quality Assurance (AUN-QA). Third, preparing learners to have open attitude, live in harmony in the multicultural society and able to behave cooperatively in maintaining morality values.Â Â